2015
DOI: 10.1248/bpb.b15-00057
|View full text |Cite
|
Sign up to set email alerts
|

High Expression Levels of Trigger Receptor Expressed on Myeloid Cells-1 on Neutrophils Associated with Increased Severity of Acute Pancreatitis in Mice

Abstract: Triggering receptor expressed on myeloid cells (TREM)-1 expression on neutrophils is associated with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The triggering receptor expressed on myeloid cell 1 (TREM1) is a membrane receptor associated with inflammation and infection. It has been reported that Soluble TREM-1 contributes to the rapid and accurate diagnosis of necrotic tissue secondary infection in patients with SAP ( Liu, et al, 2015 ). TREM-1 is also a key molecule mediating AP-associated intestinal barrier damage ( Dang, et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The triggering receptor expressed on myeloid cell 1 (TREM1) is a membrane receptor associated with inflammation and infection. It has been reported that Soluble TREM-1 contributes to the rapid and accurate diagnosis of necrotic tissue secondary infection in patients with SAP ( Liu, et al, 2015 ). TREM-1 is also a key molecule mediating AP-associated intestinal barrier damage ( Dang, et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%